The Central European City and Its Identity (Politeja, 2018)
The form and shape of the city are, in a way, the sum of the development of its civilisation, and this is why urbanisation is so often cited as a symbol of Europe’s cultural advancement. A particular triumph of urbanisation is the concept known as “creative cities”, that is, cities that contribute creatively to the universal values of our civilisation without losing any of their local flavour or compromising their unique identity. This paper claims that the best evidence of Central Europe’s achievements as a civilisation, and the essence of its identity, are its cities. Indeed, an understanding of the phenomenon of these cities, in particular their changing meanings and stories, and a broader historical perspective on the changing nature of their functions in relation to Europe’s settlement network, are crucial to comprehending the very essence of Central European identity.